1.) expand
3x - 15 - 5x = 25 + 6x
2.) simplify
-2x - 15 = 25 + 6x
3.) add 2x to both sides
-15 = 25 + 6x + 2x
4.) simplify
-15 = 25 + 8x
5.) subtract 25 from both sides
-15 - 25 = 8x
6.) simplify -15 - 25 to -40
-40 = 8x
7.) divide both sides by 8
-40/8 = x
8.) x = -5
$20 bought 16 songs
Therefore each song costs $20/16 = $5/4 = $1.25
So:
2 songs would cost 2 * $1.25
3 songs would cost 3 * $1.25
...
x songs would cost x * $1.25
Since Renata started with $20, then her balance (y) after buying x songs would be:
y = 20 - 1.25*x
Answer:
C
If x = o then f(0) = 4(2) * 0 = 0
If f(x) = 4(2) 0 - 13
then f(x) = -13 at x = 0
For this case we have the following expression:
![(2 \sqrt {27}) (3 \sqrt {32})](https://tex.z-dn.net/?f=%282%20%5Csqrt%20%7B27%7D%29%20%283%20%5Csqrt%20%7B32%7D%29)
We have to:
![27: 3 * 3 * 3: 3 ^ 2 * 3\\32: 16 * 2: 4 ^ 2 * 2](https://tex.z-dn.net/?f=27%3A%203%20%2A%203%20%2A%203%3A%203%20%5E%202%20%2A%203%5C%5C32%3A%2016%20%2A%202%3A%204%20%5E%202%20%2A%202)
Rewriting the expression and simplifying we have:
![(2 \sqrt {3 ^ 2 * 3}) (3 \sqrt {4 ^ 2 * 2}) =\\(2 * 3 \sqrt {3}) (3 * 4 \sqrt {2}) =\\(6 \sqrt {3}) (12 \sqrt {2}) =\\72 \sqrt {3 * 2} =\\72 \sqrt {6}](https://tex.z-dn.net/?f=%282%20%5Csqrt%20%7B3%20%5E%202%20%2A%203%7D%29%20%283%20%5Csqrt%20%7B4%20%5E%202%20%2A%202%7D%29%20%3D%5C%5C%282%20%2A%203%20%5Csqrt%20%7B3%7D%29%20%283%20%2A%204%20%5Csqrt%20%7B2%7D%29%20%3D%5C%5C%286%20%5Csqrt%20%7B3%7D%29%20%2812%20%5Csqrt%20%7B2%7D%29%20%3D%5C%5C72%20%5Csqrt%20%7B3%20%2A%202%7D%20%3D%5C%5C72%20%5Csqrt%20%7B6%7D)
Answer:
![72 \sqrt {6}](https://tex.z-dn.net/?f=72%20%5Csqrt%20%7B6%7D)
Move the decimal five places until it is after one number, and because the number got bigger, your exponent is a negative.